Nitric oxide and oxidative stress (H2O2) control mammalian iron metabolism by different pathways. - Pantopoulos, K (1996)
Several cellular mRNAs are regulated posttranscriptionally by iron-responsive elements (IREs) and the cytosolic IRE-binding proteins IRP-1 and IRP-2. Three different signals are known to elicit IRP-1 activity and thus regulate IRE-containing mRNAs: iron deficiency, nitric oxide (NO), and the reactive oxygen intermediate hydrogen peroxide (H2O2). In this report, we characterize the pathways for IRP-1 regulation by NO and H2O2 and examine their effects on IRP-2. We show that the responses of IRP-1 and IRP-2 to NO remarkably resemble those elicited by iron deficiency: IRP-1 induction by NO and by iron deficiency is slow and posttranslational, while IRP-2 induction by these inductive signals is slow and requires de novo protein synthesis. In contrast, H2O2 induces a rapid posttranslational activation which is limited to IRP-1. Removal of the inductive signal H2O2 after < or = 15 min of treatment (induction phase) permits a complete IRP-1 activation within 60 min (execution phase) which is sustained for several hours. This contrasts with the IRP-1 activation pathway by NO and iron depletion, in which NO-releasing drugs or iron chelators need to be present during the entire activation phase. Finally, we demonstrate that biologically synthesized NO regulates the expression of IRE-containing mRNAs in target cells by passive diffusion and that oxidative stress endogenously generated by pharmacological modulation of the mitochondrial respiratory chain activates IRP-1, underscoring the physiological significance of NO and reactive oxygen intermediates as regulators of cellular iron metabolism. We discuss models to explain the activation pathways of IRP-1 and IRP-2. In particular, we suggest the possibility that NO affects iron availability rather than the iron-sulfur cluster of IRP-1.